Live as you wish and ruin your life : Haybron on unhappiness and well-being - Garciá Báez, Norberto (2014)
This thesis examines the concepts of happiness, unhappiness and well-being developed by philosopher Daniel Haybron in his book The Pursuit of Unhappiness. The central thesis of this book is that human beings are not psychologically well-adapted to live in liberal societies, which are understood in this approach as option-rich environments. According to Haybron, in liberal societies people have freedom to choose whatever they want from a myriad of options in the pursuit of happiness. This condition, however, makes people prone to committing serious mistakes in choosing the options that are prudentially good for them. Haybron calls this phenomenon “systematic imprudence.” This systematic imprudence is the main explanation for the high rate of unhappiness and ill-being in liberal societies.